Perencanaan Struktur Gedung Apartemen New Tanjung Semarang (Indonesian Journal of Civil Engineering Study, 2025)
Due to the limited units in the Tanjung Semarang apartment and the large amount of interest from the public, PT. Bank Mandiri (Persero) Tbk decided to build the New Tanjung Semarang apartments in the same area as the Tanjung Semarang apartments. This report aims to plan the structure of the New Tanjung Semarang Apartment Building as an answer to PT. Bank Mandiri for the large amount of public interest in the Tanjung Semarang apartment. The analytical method is a method used in planning the structural construction of the New Tanjung Semarang Apartment building so that with this method it can be carried out in a structured manner so that the implementation can run smoothly. The structural planning of the building refers to SNI 1726:2019—Structural Concrete Requirements for Buildings, SNI 1727:2020—Minimum Loading Regulations, and SNI 2847:2019—Structural Concrete Requirements for Buildings. These standards are essential for ensuring the safety and stability of buildings in Indonesia. The result of this planning is to obtain the structural elements needed to plan the structure of the New Tanjung Semarang apartment building.
Keywords: Apartment; Structure; Planning